Class III orthognathic surgical cases facilitated by accelerated osteogenic orthodontics: a preliminary report - Wu JiaQi; Xu Li; Liang Cheng; Jiang JiuHui (Sciendo, 2015)
To describe a multidisciplinary treatment approach that includes corticotomy, orthodontic force and orthognathic surgery for the management of skeletal Class III surgical cases. The main advantage of the combined techniques is a reduction in treatment time for young adult patients.